The Perpetuation of a School Culture that Doesn't Support Collaboration on the Learning Opportunity Gap between Students - Gani, Abdul; Irfan, Mochamad (Metromedia, 2022)
This study examines the influence of a school culture that does not support collaboration on the learning opportunity gap between students with different social and academic backgrounds. A school culture that prioritizes individual competition and does not encourage cooperation between students has the potential to exacerbate inequalities in learning. In such an environment, students from weaker social or academic backgrounds often do not get an equal opportunity to interact and learn together with more fortunate students. As a result, they become isolated and lose opportunities to improve their academic understanding, which further widens the gap in academic achievement. This research highlights the importance of creating a culture that supports collaboration in the classroom, which can provide greater opportunities for all students, including those who are marginalized, to learn together and share knowledge with each other. Collaboration between students is the key to reducing this inequality and improving the overall quality of learning. Schools need to adopt a more inclusive approach, one that prioritizes collaboration and cooperation among students to facilitate more equitable and equitable learning opportunities. In addition, it is important for teachers to be involved in training on how to support collaborative learning in the classroom.